Unusual Presentation of Gianotti-Crosti Syndrome due to Epstein-Barr Virus Infection - Hind Saif Al Dhaheri; Amani Al Kaabi; Yasmin Kara Hamo; Aysha Al Kaabi; Salwa Al Kaabi; Hossam Al Tatari (Case Reports in Dermatological Medicine)
Gianotti-Crosti syndrome (GCS) is viral exanthema of childhood. It typically presents with a symmetric erythematous papular and papulovesicular eruption. It has been classically associated with hepatitis B virus, as well as rarely with Epstein-Barr virus (EBV). We report a case of GCS related to EBV infection without the classical systemic symptoms in a five-year-old male patient.